Interrelationships and Methods for Improving University Students' Sense of Gain, Sense of Security, and Happiness - Feng, Linlin; Zhong, Hao (Frontiers in Psychology, 2021)
The report of the 19th National Congress of the Communist Party of China stressed the necessity to “keep up with people’s ever-growing needs for a better life. We will continue to promote social fairness and justice, develop effective social governance, and maintain public order. With this we should see that our people will always have a strong sense of gain, happiness, and sense of security”. In this study, 646 university students were surveyed using the Demographic Questionnaire, Sense of Gain Scale, Sense of Security Scale, Orientations to Happiness Scale, and Prosocial Behavior Tendencies Scale to explore the relationships between sense of gain, sense of security and happiness (including meaning, pleasure, and engagement happiness), and to discuss methods for enhancing them on the basis of prosocial behaviors. The results revealed that (1) sense of gain had significant positive correlations with meaning, pleasure, and engagement happiness but a significant negative correlation with sense of security. Sense of security did not have a significant correlation with the three types of happiness. Prosocial behaviors had a significant positive correlation with sense of gain and the three types of happiness but shared no significant correlation with sense of security. (2) Sense of gain significantly and positively predicted meaning, pleasure, and engagement happiness, whereas the interaction between sense of security and sense of gain did not yield a significant prediction for the three types of happiness. Prosocial behaviors significantly and positively predicted sense of gain and the three types of happiness. (3) Sense of gain had a mediating effect on the relationships between prosocial behaviors and meaning, pleasure, and engagement happiness, whereas sense of security did not have a moderating effect on the relationships between sense of gain and the three types of happiness. Prosocial behaviors directly affect meaning, pleasure, and engagement happiness and can indirectly influence happiness through enhancing a sense of gain. The implementation of prosocial behaviors can not only provide help for others, but also promote the self-satisfaction of the behavior agents and help them get more happiness.